An Action Research to Map and Describe the Business Ecosystem of Muslim Fashion Industry in Bandung in Form of a Short Movie - Monika, Gelda Sella; Lantu, Donald Crestofel (Journal of Business and Management, 2015)
Abstract. Bandung has the vision to be the Muslim fashion Capital in 2020 since it has the strengths and opportunities for it.  However, this vision needs to be supported by the proper programs and strategy from collaborated elements in Quadro Helix which are the government, academicians, business players, and communities. Therefore, the business ecosystem needs to be described first in order to get the clear understanding of the current condition of Muslim fashion Industry in Bandung. Through a qualitative action research method, the author conducted the research to map and describe the business ecosystem of Muslim fashion industry in Bandung in form of a short movie. The short movie is purposed as an attractive learning tool that can inform and inspire those who want to start or already in Muslim fashion business. The decision to use short movie was based on some researches that show the use of film in education and it is based on the decision of CIEL SBM ITB as the problem owner.  Due to the limitation on research budget and time, this action research is only focused to create a project proposal of a short movie that includes story idea, screenplay and director’s treatment, without truly producing it. By using focus group discussion and semi-structured interviews, data is collected and analyzed by using narrative analysis method. As the result, the movie should fulfill the criteria: inspirational and educative, attractive to watch, and also beneficial to the sponsors. So, the author must develop the story idea become somewhat an appropriate screenplay and director’s treatment to match with those criteria. The content of the movie also must summarize the findings about the current condition of Muslim fashion industry in Bandung, and the role of each element in Quadro Helix model for the Muslim fashion industry. Last, the short movie must insert suggestion and the keys success for those who want to enter or already in the business as well.  Keywords: Business Ecosystem, Muslim Fashion Industry, Bandung, Action Research.